Clearing crimes in the aftermath of police lethal violence - Roberts, Aki (Criminology & public policy, 2022)
Research summary Police use of violence may threaten police agencies’ effectiveness by reinforcing residents’ legal cynicism and disengagement from police. We examined police lethal violence against Black people and its relationship with clearance by arrest in a sample of Black victims’ crime incidents in over 350 jurisdictions in 2015, via Mapping Police Violence and the National Incident-Based Reporting System (NIBRS). We calculated each crime incident's unique time-varying exposure to police lethal violence, with an accompanying agency-level measure that averaged this incident-level measure. Under our original measures, multilevel survival analysis showed a statistically significant association with clearance for the agency-level average exposure measure, but not for the time-varying incident-level exposure measure. Subsequent exploratory analyses suggested a possibly shorter-lived relationship with incident-level police lethal violence exposure, which should be investigated in future research. Policy implications Agency-level findings encourage the adoption of reforms in policing practices and organizational characteristics that could enhance police legitimacy and citizen cooperation and promote perceptions of procedural justice in the Black community. Exploratory indications of a shorter-lived relationship between police lethal violence and clearance will, if supported in further research, call for agencies to think carefully about adjusting detective work and resource allocations during the critical period following a police lethal violence event. A negative relationship between clearance rates and police lethal violence suggests a mutual interest of police agencies and activists in the reduction of police lethal violence.